2015
DOI: 10.1016/j.powtec.2015.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanical vibration on the size and microstructure of titania granules produced by auto-granulation

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The primary particle size is reported to be around 0.1 m, although it is likely that the powder will be endowed with a certain degree of agglomeration even before starting the vibration process. In Figure 1, the solid fractions calculated with dp=2.1 m from Eq.4 are reported as a function of V. In the same figure, the average values of the experimental solid fractions obtained from Ku et al [1] are shown for comparison. Inspection of Figure 1 reveals that the proposed model is capable of capturing the variation of the packing fraction with the vibration intensity apart from one data point.…”
Section: Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary particle size is reported to be around 0.1 m, although it is likely that the powder will be endowed with a certain degree of agglomeration even before starting the vibration process. In Figure 1, the solid fractions calculated with dp=2.1 m from Eq.4 are reported as a function of V. In the same figure, the average values of the experimental solid fractions obtained from Ku et al [1] are shown for comparison. Inspection of Figure 1 reveals that the proposed model is capable of capturing the variation of the packing fraction with the vibration intensity apart from one data point.…”
Section: Validationmentioning
confidence: 99%
“…The model is first validated with the experimental data provided by Ku et al [1]. The primary particle properties are given in Table 1.…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…The appearance of the powder is white and cohesive, with loose clusters easily forming during powder handling and storage. Titania has the ability to autoagglomerate, due to possible agitation of the powder bed, such as mechanical vibration [6].…”
Section: Materials Usedmentioning
confidence: 99%